Improvements on the present theoretical understanding of octupole correlations - Robledo L.M. (EPJ Web of Conferences, 2014)
Some intriguing results, obtained in a recent survey of octupole properties for all even-even nuclei, are reanalyzed in order to understand the origin of the strong disagreement with experimental data and/or the strange behaviours observed. The limitations of the rotational formula to describe E1 and E3 transition strengths are discussed as well as the role played by octupole-quadrupole coupling in some specific nuclei.